Malaysian parents’ bank selection criteria for their children - Mohammad Fauzi, Fatin Aliaa (2023)
In these modern times, with the emergence of many financial institutions with different product and service offerings, parents have various choices of products and services to select for their children. This dissertation research attempts to provide the foundation of bank selection criteria studies in the context of Malaysian parents and their children. This paper presents the most important factor influencing Malaysian parents in selecting a bank for their children in Malaysia. In particular, the study examines the impact of various bank selection criteria, namely convenience, tangibles, reliability, banking innovation, responsiveness, recommendation, bank image, and customer satisfaction, on customer loyalty in the banking sector of Malaysia. This research also investigates the mediation and moderation relationship on customer loyalty. The dissertation research distributed an online questionnaire using Qualtrics among Malaysian parents and obtained 187 usable responses. The research data were analysed using a reliability test, Pearson's correlation analysis, principal components analysis (PCA), varimax orthogonal rotation, analysis of variance (ANOVA), and Mediation and Moderation analysis. The finding reports that reliability, recommendation, and banking innovation are significant choice criteria. Moreover, the five more important criteria are the availability of internet banking and mobile banking services, guaranteed bank security, genuine interest in solving customers’ problems, prompt service from the bank’s employees, and delivering service when it promises to do so. In addition, other gender plays a moderating role, and recommendation holds a mediating role.